(untitled) (Research, Society and Development, 2023)
Proton pump inhibitors (PPIs) are the most widely used drugs in the world. Currently, six PPIs are available on the market: dexlansoprazole, esomeprazole, lansoprazole, pantoprazole, omeprazole and rabeprazole. Their half-life is approximately 1 hour and they are biotransformed in the liver through CYP2C19 and CYP3A4 isoforms. The objective was to carry out a literature review regarding the pharmacokinetics, side effects and effectiveness of IBPS. The methodology was based on an integrative review, which considered the databases Medline, Lilacs, Scielo, Pubmed and Google Scholar, articles in English, Portuguese and Spanish, published from 2011 to 2019. PPIs are abrasive drugs used in the treatment of diseases applied to gastric acid secretion, having a good potential in inhibiting acid secretion, which may take up to 3 to 4 days. PPIs are generally well tolerated, and the most common side effects are headache, abdominal pain, nausea, and diarrhea. PPIs produce significantly more effective and prolonged acid suppression than H2 receptor antagonists and can maintain gastric pH above 4 for up to 16 to 18 h/day. In the context of what has been presented, PPIs have been the drugs of first choice in the treatment of peptic diseases. They are generally well accepted, and care should be taken in patients who take this medication for 1 year or more.